2020
DOI: 10.1111/1751-2980.12881
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional imaging for assessing intestinal fibrosis in Crohn's disease

Abstract: More than 30% of patients with Crohn's disease (CD) develop fibrotic strictures in the bowel as the disease progresses. Excessive deposition of extracellular matrix components in the submucosa and smooth muscle hypertrophy or hyperplasia are the main features of fibrosis in CD. Cross‐sectional imaging technology provides a wealth of information on the anatomy, histological composition, and physiological function of the bowel, allowing for a non‐invasive and complete evaluation of associated abnormalities. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…There is persisting need for imaging techniques that could quantify the amount of fibrotic tissue in strictures and assist the decision of medical or surgical management. There have been advances in assessment of fibrostenotic Crohn’s disease using cross-sectional imaging techniques [ 17 ]. Diffusion MR techniques are promising, but could not be applied to our model due to the small size of the animal colons and the “noise” due to the diffusion technique [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is persisting need for imaging techniques that could quantify the amount of fibrotic tissue in strictures and assist the decision of medical or surgical management. There have been advances in assessment of fibrostenotic Crohn’s disease using cross-sectional imaging techniques [ 17 ]. Diffusion MR techniques are promising, but could not be applied to our model due to the small size of the animal colons and the “noise” due to the diffusion technique [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study with a small sample size 42 demonstrated that the ratio of mesenteric tissue to intestinal wall stiffness measured by ultrasound elastography was useful for assessing the degree of intestinal fibrosis in CD with strictures. In addition, photoacoustic imaging can also quantify the composition of intestinal stricture, and is expected to distinguish inflammatory components from fibrotic ones 43 …”
Section: Assessment Of Intestinal Stricturementioning
confidence: 99%
“…However, as most of the patients included had moderate to severe fibrosis, this new method needs to be further verified in patients with early CD and fibrosis. Inflammatory strictures can also be distinguished from fibrotic ones in CD by other combination modalities, such as the magnetization transfer (MT) ratio of magnetization transfer imaging with T2WI of conventional MRI 46 and dynamic contrast‐enhanced MRI with intravoxel in coherent motion 43 . In addition, MRE may predict disease progression and the need for future surgery in CD with strictures; surgery‐related MRE features include proximal bowel dilatation diameter ≥30 mm, stricture wall thickness ≥10 mm and stricture length >5 cm 47 …”
Section: Assessment Of Intestinal Stricturementioning
confidence: 99%
“…As stricturing bowel segments contain variable proportions of in ammatory and brotic tissue, brosis quanti cation is challenging. 11,12 However, differentiating brotic strictures from in ammatory narrowing of the bowel lumen is clinically important because symptomatic brotic strictures are currently an indication for endoscopic balloon dilatation or surgery, while in ammatory strictures may bene t from conventional anti-in ammatory therapy. Endoscopic assessment of brosis in strictures is ine cient because of the transmural nature of the lesions in CD.…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques cannot accurately measure the amount of brosis in a stricture. 3,11,14,15 Magnetic resonance imaging (MRI) has gained broad acceptance as the reference technique for assessing the disease extent and activity in CD, especially due to its lack of radiation exposure. 15 Routinely used magnetic resonance (MR) sequences have also been used to quantify intestinal brosis in CD, but inconsistent data have been reported, as superimposed in ammation can mask transmural brosis.…”
Section: Introductionmentioning
confidence: 99%